The Psychometric Properties of the Patient Health Questionnaire-9 in a Sample of Korean University Students - Kim, Yang Eun (Psychiatry Investig, 2019)
OBJECTIVE: Depressive symptoms among university students are a major mental-health issue worldwide, and university students are particularly vulnerable to various stressors that can produce depression. Therefore, accurate and sustainable assessment of depressive symptoms among university students is of special importance. The Patient Health Questionnaire-9 (PHQ-9) is one such measure. The objective of the current study was to evaluate the psychometric properties of the PHQ-9 among Korean university students. METHODS: A total sample of 582 university students attending a four-year private university in South Korea was recruited for the study. Confirmatory factor analyses (CFAs) were performed to compare the goodness-of-fit of four competing models suggested by extant literature on the PHQ-9. Convergent validity was assessed using a correlation analysis between the PHQ-9 and other psychiatric instruments, including the Depression, Anxiety, and Stress Scale-21 (DASS-21) and the Generalized Anxiety Disorder Scale (GAD-7). RESULTS: A one-factor structure of the PHQ-9 provided the best fit to the data. Internal consistency was adequate. The PHQ-9 demonstrated good convergent validity with related constructs. CONCLUSION: The psychometric properties of the PHQ-9 proved to be adequate, with a robust and interpretable factor structure and good internal consistency. The PHQ-9’s validity, reliability, brevity and ease of administration make it a useful screening instrument for depression among university students in Korea.